2-Cysteine Peroxiredoxins and Thylakoid Ascorbate Peroxidase Create a Water-Water Cycle That Is Essential to Protect the Photosynthetic Apparatus under High Light Stress Conditions. Issue 4 (9th February 2015) - Awad, Jasmin; Stotz, Henrik U.; Fekete, Agnes; Krischke, Markus; Engert, Cornelia; Havaux, Michel; Berger, Susanne; Mueller, Martin J.
Abstract : 2-Cys peroxiredoxins and thylakoid ascorbate peroxidase act together to protect plants against high light damage by creating a water-water cycle and restricting light-induced redox signaling. Abstract: Different peroxidases, including 2-cysteine (2-Cys) peroxiredoxins (PRXs) and thylakoid ascorbate peroxidase (tAPX), have been proposed to be involved in the water-water cycle (WWC ) and hydrogen peroxide (H2 O2 )-mediated signaling in plastids. We generated an Arabidopsis ( Arabidopsis thaliana ) double-mutant line deficient in the two plastid 2-Cys PRXs (2-Cys PRX A and B, 2cpa 2cpb ) and a triple mutant deficient in 2-Cys PRXs and tAPX ( 2cpa 2cpb tapx ). In contrast to wild-type and tapx single-knockout plants, 2cpa 2cpb double-knockout plants showed an impairment of photosynthetic efficiency and became photobleached under high light (HL ) growth conditions. In addition, double-mutant plants also generated elevated levels of superoxide anion radicals, H2 O2, and carbonylated proteins but lacked anthocyanin accumulation under HL stress conditions. Under HL conditions, 2-Cys PRXs seem to be essential in maintaining the WWC, whereas tAPX is dispensable. By comparison, this HL -sensitive phenotype was more severe in 2cpa 2cpb tapx triple-mutant plants, indicating that tAPX partially compensates for the loss of functional 2-Cys PRXs by mutation or inactivation by overoxidation. In response to HL, H2 O2 - and photooxidative stress-responsive marker genes were found to be dramatically up-regulated in 2cpa 2cpb tapx but not 2cpa 2cpb mutant plants, suggesting that HL -induced plastid to nucleus retrograde photooxidative stress signaling takes place after loss or inactivation of the WWC enzymes 2-Cys PRX A, 2-Cys PRX B, and tAPX.